Giełdy towarowe w Polsce w procesie gospodarczej integracji Unii Europejskiej - Drewiński, Marek (Commodity Exchange in Poland and Integrations Process in the European Union (the Example of Commodity Markets), 2007)
The paper is an attempt of bringing close some problems of organization and functioning the market institutions in integration process in the European Union. Thanks to their importance in the international trade, commodity exchange will have in this matther a particular part to play. The purpose of this paper is thus evaluation of the present state of commodity exchanges in Poland as projected against the background of experiences gathered during the operation of commodity exchanges in the member countries of the European Community. Finally, the required reconstructuring directions of Polish commodity exchanges are given, which will favour a fast integration of Polish economy into the structures of the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 257-269